(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Significantly increases the penetration of wind energy as one of the renewable energy sources to cover the load on the demand side of electricity. Therefore, it is important to study the effect of wind energy on the dynamic stability of the electrical system. The growing demand for energy has led to the development of new technologies, which play a leading role in shaping the future of the energy market. Due to the constraints of the particular medium surrounding the wind turbine is connected to a network, they promise to improve the reliability of the system. When the wind is introduced into the grid, it affects the quality of the energy. Power Quality measurements effects are active power, reactive power, voltage fluctuation, flicker, harmonic and electrical behavior of switching operations. This paper presents the effect of static compensators (STATCOM) as the stability of power systems associated with wind power conversion systems. STATCOM (synchronous static compensator) is connected to a voltage source Converter (VSC) with the automatic switching device and can be used effectively to compensate reactive power. This article presents a STATCOM wind energy system at the general connection point to mitigate power quality problems. A STATCOM control system for a grid connected wind system is modeled using MATLAB / Simulink to improve network power quality. The results of the simulation show the performance of STATCOM.